An Assessment of Harm in Adults—Adverse Childhood Experiences Screening in Primary Care: A Survey-Based Study - Katelyn M. Inch MSc; Craig Olmstead MD, CCFP; Brenna A. Kaschor MD, PhD, CCFP (Journal of Patient Experience, 2025)
The Adverse Childhood Experiences Questionnaire (ACE-Q) screens for adverse childhood experiences (ACEs), which are linked to increased disease risk. Although pediatric studies report no adverse effects of ACE-Q use, primary care data is limited. This study examined adult patients’ experiences with ACE-Q screening in primary care. Adults (18+) at a primary care center in London, Ontario, completed the ACE-Q and a follow-up questionnaire evaluating ACE screening experience. Correlations assessed relationships between ACE-Q scores and follow-up responses. Among 260 participants, 81% reported at least one ACE. Most (82%) felt comfortable discussing stressful childhood experiences with their healthcare provider. Higher ACE scores were associated with increased discomfort (r s  = −0.166, P  = 0.007), feeling upset by the ACE-Q (r s  = 0.173, P  = 0.005), and greater interest in learning about ACEs (r s  = 0.177, P  = 0.004). Overall, ACE-Q screening in primary care was generally well-received, with most patients recognizing its relevance despite some discomfort. These findings highlight the potential for integrating ACE screening into routine primary care to address long-term health risks. Further research is needed to confirm findings and optimize screening practices.